The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fimmu.2019.00783
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Dynamically Regulates Inflammation and Development of Brain-Resident Memory CD8 T Cells During Persistent Viral Encephalitis

Abstract: Programmed cell death-1 (PD-1) receptor signaling dampens the functionality of T cells faced with repetitive antigenic stimulation from chronic infections or tumors. Using intracerebral (i.c.) inoculation with mouse polyomavirus (MuPyV), we have shown that CD8 T cells establish a PD-1 hi , tissue-resident memory population in the brains (bT RM ) of mice with a low-level persistent infection. In MuPyV encephalitis, PD-L1 was expressed on infiltrating myeloid cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 85 publications
4
46
0
Order By: Relevance
“…There are a number of inhibitory receptors expressed by CD8 T RM that likely serve to keep these cells at bay until bona fide antigen recognition occurs through the TCR. Brain T RM cells express PD1, a receptor associated with T cell exhaustion and inability to activate [53,54]. Blockade of PD-1 ligand in tumor settings greatly enhances T cell elimination of cancer cells [55].…”
Section: Mechanisms That Suppress T Rm Activation May Have Other Funcmentioning
confidence: 99%
“…There are a number of inhibitory receptors expressed by CD8 T RM that likely serve to keep these cells at bay until bona fide antigen recognition occurs through the TCR. Brain T RM cells express PD1, a receptor associated with T cell exhaustion and inability to activate [53,54]. Blockade of PD-1 ligand in tumor settings greatly enhances T cell elimination of cancer cells [55].…”
Section: Mechanisms That Suppress T Rm Activation May Have Other Funcmentioning
confidence: 99%
“…Adoptive transfer studies of bT RM and the finding that the Pdcd1 locus of brain CD8 T cells, but not spleen CD8 T cells, was demethylated supports that PD-1 expression is intrinsic to bT RM [38]. Nanostring gene expression analysis of the PD-L1 −/− brain microenvironment suggests that the PD-1:PD-L1 pathway decreases neuroinflammation during MuPyV infection [43], further indicating that PD-1 on bT RM protects against CNS damage. T cells isolated from 26 post-mortem brains from patients who died of non-CNS disease showed that both PD-1 and CTLA-4 are expressed by human brain CD8 T cells, but not CD8 T cells in blood [67].…”
Section: Pd-1 As Neuroprotectivementioning
confidence: 78%
“…A recent study of T cells in human brains also found a 40/60% split of CD103 + /CD103 − CD8 T cells; there, CD103 expression correlated with upregulation of homing markers, but without a difference in localization [67]. Interestingly, in both mice and humans, there appears to be an inverse relationship between PD-1 and CD103 expression by CD8 T RM [43,68]. Thus, CD103 expression is an imperfect T RM marker and may not be involved in CNS localization; moreover, whether PD-1 regulates CD103 expression or possibly fosters survival of CD103 − CD8 T cells remains to be determined.…”
Section: Cd103 In the Cnsmentioning
confidence: 89%
See 2 more Smart Citations